AN OPEN RANDOMISED CONTROL TRAIL TO EVALUATE THE LITHOTRIPTIC ACTION OF SHIGRU MULA KWATH ON UROLITHIASIS - Sarika, *Singh; Azeem, Ahmad (International Journal of Ayurveda and Pharma Research, 2016)
Urolithiasis is a multifactorial disease that remains a significant health problem. It carries significant morbidity and imposes tremendous financial burden on healthcare system. A variety of intrinsic and extrinsic factors influence the incidence of disease. Management of urolithiasis depends on size and location of stone. Stone larger than 5 mm, which fails to pass through urinary system, should be treated by some interventional procedure such as Extracorporeal Shock Wave Lithotripsy (ESWL), Ureteroscopy, Percutaneous Nephrolithotomy.Unfortunately the propensity for stone recurrence is not altered by removal of stone by these procedures and recurrence is still about 50% within 10 years. In addition these interventional procedures show some significant side effects. For prevention or recurrence of stone many herbal medicines have been traditionally used to treat kidney stones and have been shown to be effective. Acharya Vagbhatta has explained in Ashmari Chikitsa adhyaya that intake of lukewarm decoction of root of Moringa oleifera (Shigru) have lithotriptic action. Considering the above reference the present study was carried out to evaluate lithotriptic action of Moringa oleifera as it is cheap, easily available and palatable.Result & Conclusion: This study shows that Shigru Mula Kwath is as effective as compared to Varunadi Kwath, also Shigru Mula Kwath significantly helped to reduce the signs, symptoms and help to disintegrate the calculus. The prospective aspect of this study reveals that Shigru Mula Kwath can be used as lithotriptic, diuretic, alkalizer and analgesic to treat the Ashmari effectively.